Assessing the Impact of Legislative Budget Allocations on Community Aspiration Fulfillment - Chairul Abd. Halik; Irfan Zamzam; Hartaty Hadady; Sharina Osman (Jurnal Ilmiah Akuntansi, 2024)
While existing research has explored the effectiveness of the recess budget of Regional People's Representative Council (Dewan Perwakilan Rakyat Daerah—DPRD) members in absorbing community aspirations in regions in Indonesia, there is a specific need to examine the alignment of budget expenditures with actual outcomes. This study assesses how effectively the DPRD members of North Maluku use the recess budget to capture community aspirations and prioritize them within DPRD’s strategic plans. Utilizing a qualitative, phenomenological approach, the research involved DPRD members, the Local Government Budget Team, and experts or academics. Data were gathered through interviews and documentation, analyzed using Miles and Huberman’s interactive model. The findings indicate that the recess budget has been used effectively, meeting all eight effectiveness criteria. The process of prioritizing community aspirations in the development of DPRD’s strategic agenda is done subjectively by DPRD members, focusing on urgent needs in alignment with the priorities of the Regional Medium-Term Development Plan (Rencana Pembangunan Jangka Menengah Daerah—RPJMD), and influenced by the initial locations visited during recess, discussions with the community, and direct engagement with relevant community issues.